The impact of auditory working memory training on the fronto-parietal working memory network - Schneiders, Julia; Opitz, Bertram; Tang, Huijun; Deng, Yuan; Xie, Chiaoxiang; Li, Hong; Mecklinger, Axel (Frontiers in Human Neuroscience, 2012)
Working memory training has been widely used to investigate working memory processes. We have shown previously that visual working memory benefits only from intra-modal visual but not from across-modal auditory working memory training. In the present functional magnetic resonance imaging study we examined whether auditory working memory processes can also be trained specifically and which training-induced activation changes accompany theses effects. It was investigated whether working memory training with strongly distinct auditory materials transfers exclusively to an auditory (intra-modal) working memory task or whether it generalizes to a (across-modal) visual working memory task. We used adaptive n-back training with tonal sequences and a passive control condition. The memory training led to a reliable training gain. Transfer effects were found for the (intra-modal) auditory but not for the (across-modal) visual transfer task. Training-induced activation decreases in the auditory transfer task were found in two regions in the right inferior frontal gyrus. These effects confirm our previous findings in the visual modality and extents intra-modal effects in the prefrontal cortex to the auditory modality. As the right inferior frontal gyrus is frequently found in maintaining modality-specific auditory information, these results might reflect increased neural efficiency in auditory working memory processes. Furthermore, task-unspecific (amodal) activation decreases in the visual and auditory transfer task were found in the right inferior parietal lobule and the superior portion of the right middle frontal gyrus reflecting less demand on general attentional control processes. These data are in good agreement with amodal activation decreases within the same brain regions on a visual transfer task reported previously.